2021
DOI: 10.1128/mbio.00288-21
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Transmission of a Measles Virus Vaccine Strain from Neurons to Astrocytes

Abstract: Viruses, including members of the herpes-, entero-, and morbillivirus families, are the most common cause of infectious encephalitis in mammals worldwide. During most instances of acute viral encephalitis, neurons are typically the initial cell type that is infected. However, as replication and spread ensue, other parenchymal cells can become viral targets, especially in chronic infections. Consequently, to ascertain how neurotropic viruses trigger neuropathology, it is crucial to identify which central nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…For example, for viruses that are assembled and released from the cell surface, mutations that limit or prevent cell surface expression of viral proteins can prevent recognition by antibodies. In the measles virus-induced late disease SSPE, virion proteins required for particle assembly at the plasma membrane (hemagglutinin, fusion, and matrix) have acquired changes that prevent cell surface expression and virion assembly but promote cell-to-cell ribonucleoprotein transfer to uninfected cells, thereby allowing continued spread of viral RNA without producing infectious virions [ 121 124 ]. Similar mutations have been observed in the viral RNAs from persistent CNS infections due to mumps and mouse hepatitis viruses [ 113 , 125 ].…”
Section: How Do Rna Viruses Evade the Immune System To Persist?mentioning
confidence: 99%
“…For example, for viruses that are assembled and released from the cell surface, mutations that limit or prevent cell surface expression of viral proteins can prevent recognition by antibodies. In the measles virus-induced late disease SSPE, virion proteins required for particle assembly at the plasma membrane (hemagglutinin, fusion, and matrix) have acquired changes that prevent cell surface expression and virion assembly but promote cell-to-cell ribonucleoprotein transfer to uninfected cells, thereby allowing continued spread of viral RNA without producing infectious virions [ 121 124 ]. Similar mutations have been observed in the viral RNAs from persistent CNS infections due to mumps and mouse hepatitis viruses [ 113 , 125 ].…”
Section: How Do Rna Viruses Evade the Immune System To Persist?mentioning
confidence: 99%
“…It is known that viruses may persist and slowly spread from cell to cell without the production of an infectious virus [44][45][46]. To establish persistent infections, viruses must avoid elimination by the immune response of the host; this may be achieved by establishing infections in immunologically privileged sites such as the testes.…”
Section: Discussionmentioning
confidence: 99%
“…Since neurons, which are important cell targets affected in SSPE, express neither SLAM nor nectin-4, CDV is thought to exploit a different infection mechanism that does not involve these two receptors [ 62 ]. Early research on the spread of MeV between neurons indicated that MeV adopts a trans-synaptic mode of spread and does not require CD46 expression [ 61 , 70 ]. However, viral transport across the synaptic cleft requires membrane fusion, with neurokinin-1 (NK-1)—a highly conserved protein expressed in diverse mammalian cells [ 71 ]—playing a possible key role as an MeV-F receptor.…”
Section: CDV Invasion and Pathogenicity In The Cnsmentioning
confidence: 99%